Life after conflict-related amputation trauma: a clinical study from the Gaza Strip - Hanne Edøy Heszlein-Lossius; Yahya Al-Borno; Samar Shaqqoura; Nashwa Skaik; Lasse Melvaer Giil; Mads Gilbert (BMC, 2018)
Abstract Background More than 17.000 Palestinians were injured during different Israeli military incursions on the Gaza Strip from 2006 to 2014. Many suffered traumatic extremity amputations. We describe the injuries, complications, living conditions and health among a selection of traumatic amputees in the Gaza Strip. Methods We included 254 civilian Palestinians who had survived, but lost one or more limb(s) during military incursions from 2006 to 2016. All patients were receiving follow-up treatment at a physical rehabilitation center in Gaza at the time of inclusion. We measured and photographed anatomical location and length of extremity amputations and interviewed the amputees using standard questionnaires on self-reported health, socioeconomic status, mechanism of injury, physical status and medical history. Results The amputees were young (median age 25,6 years at the time of trauma), well educated (37% above graduate level), males (92%), but also 43 children (17% ≤ 18 years). The greater part suffered major amputations (85% above wrist or ankle). Limb losses were unilateral (35% above-, 29·5% below knee), and bilateral (17%) lower extremity amputations. Pain was the most frequent long-term complaint (in joints; 34%, back; 33% or phantom pain; 40·6%). Sixty-three percent of amputees were their family's sole breadwinner, 75·2% were unemployed and 46% had lost their home. Only one in ten (11·6%) of the destroyed homes had been rebuilt. Conclusions The most frequently observed amputees in our study were young, well-educated male breadwinners and almost one in five were children. Conflict-related traumatic amputations have wide-ranging, serious consequences for the amputees and their families.